Une diplomatie du concert.: La présence musicale française au Caire dans les années 1920-1930 - Brunet, Maxendre (Manazir Journal, 2021)
Although the place of music in the French political imagination has recently been the subject of fruitful research, it remains a blind spot in the study of French cultural exchange. This can be explained by the non-verbal nature of musical events, or the relative technicality of their study. This article shows how the Association d’expansion et d’échanges artistiques contributed to the promotion of French musicians in Cairo between the late 1920s and the late 1930s.